2022
DOI: 10.3390/app12157457
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Jellyfish Optimization with Deep-Learning-Driven Decision Support System for Energy Management in Smart Cities

Abstract: A smart city is a sustainable and effectual urban center which offers a maximal quality of life to its inhabitants with the optimal management of their resources. Energy management is the most difficult problem in such urban centers because of the difficulty of energy models and their important role. The recent developments of machine learning (ML) and deep learning (DL) models pave the way to design effective energy management schemes. In this respect, this study introduces an artificial jellyfish optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This AJS is one of the newly proposed meta-heuristic swarm-based optimization algorithms derived by simulating the locomotion and dietary patterns [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] of jellyfish. Jellyfish are the most efficient swimmers of all aquatic animals widely seen in the oceans having umbrella-shaped bells and trailing tentacles.…”
Section: Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This AJS is one of the newly proposed meta-heuristic swarm-based optimization algorithms derived by simulating the locomotion and dietary patterns [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] of jellyfish. Jellyfish are the most efficient swimmers of all aquatic animals widely seen in the oceans having umbrella-shaped bells and trailing tentacles.…”
Section: Methodologiesmentioning
confidence: 99%
“…The key advantages of the ensemble learning mechanism to design a robust feature selection model by proposing combined feature fusion strategies [ 19 , 20 , 21 ], such as combined feature set (CFS), adaptive weighted feature set (AWFS), model-based optimized weighted feature set (MOWFS), and feature-based optimized weighted feature set (FOWFS), are experimented and validated. In order to reduce the losses and selection of optimized weights of those three pre-trained networks, the advantages of a new meta-heuristic optimizer artificial jellyfish optimizer (AJS) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] was used and finally, the performance of the proposed feature fusion strategies are likened to other combinations of the models with genetic algorithm (GA) [ 30 ] and particle swarm optimization (PSO) [ 31 ] such as MOWFA-GA, MOWFS-PSO, FOWFS-GA, and FOWPS-PSO, and it was observed that the proposed combination of FOWFS-AJS outperforms the other models used for classification of skin lesion diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional path planning methods mainly face an optimization task of path length and computational efficiency in dynamic and unpredictable terrains . In the multitude of algorithms proposed for path planning, bio-inspired algorithms are a powerful solution since they are flexible, scalable, and capable of finding global optima in multi-dimensional spaces [67][68][69][70][71][72][73][74][75][76][77][78]. For example, the Salp Swarm Algorithm (SSA), which is based on the swarming behavior of salps in the ocean, is one of the new bio-inspired optimization techniques that have demonstrated potential in different optimization problems [79][80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%